Integrated region-based segmentation using color components and texture featureswith prior shape knowledge - Emambakhsh, Mehryar; Ebrahimnezhad, Hossein; Sedaaghi, Mohammad Hossein (Zielona Góra: Uniwersytet Zielonogórski)
Segmentation is the art of partitioning an image into different regions where each one has some degree of uniformity in its feature space. A number of methods have been proposed and blind segmentation is one of them. It uses intrinsic image features, such as pixel intensity, color components and texture. However, some virtues, like poor contrast, noise and occlusion, can weaken the procedure.
Keywords: image segmentation; prior shape knowledge; level set; nonlinear diffusion; energy minimization